The Influence Of Work Motivation And Compensation On Employee Performance At PT. XYZ - Leryzanti, Dinda Nabila; Ariyanti, Desy; Surya, Dhea Herdianti; Haromaini, Nurul; Rahmawati, Nur Anisa (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the effect of work motivation and compensation on employee performance at PT. XYZ, a company engaged in manpower service provision (outsourcing). This study uses a quantitative approach, by obtaining data from questionnaires distributed using a saturated sampling technique, involving the entire population of 50 employees at PT. XYZ. Data analysis was performed using the Partial Least Square (PLS) method assisted by SmartPLS software. The findings reveal that work motivation has a positive and significant effect on employee performance, and compensation has a positive and significant effect on employee performance. Implementing strategies to boost motivation and establishing a fair, well-structured compensation system are vital components for the management of PT. XYZ to optimize employee performance.